Creative Tourism Destination Competitiveness - Dias, Á.; Patuleia, M. (BOOK OF ABSTRACTS of the 3rd CREATOUR International Conference and Creative Tourism Showcase: Creative Tourism Dynamics: Connecting Travellers, Communities, Cultures, and Places, 2019)
Creative tourism has been approached from several points of view: products and processes, enabling elements, marketing, sustainability, etc. However, to our best knowledge, there is no integrating model that brings together all its dimensions and enables the 'birds eye' perspective of the creative destination competitiveness. This research aims to present a model of competitiveness of a creative tourism destination. The model presents three essential dimensions: core elements (products and processes, travelers and entrepreneurs), enablers (community engagement and stakeholders competences), and developers (marketing and communication). Future research guidelines are presented based on the identification of areas to be explored in more detail.